2020
DOI: 10.1038/s41598-020-60420-9
|View full text |Cite
|
Sign up to set email alerts
|

DNA damage and expression of DNA methylation modulators in urine-derived cells of patients with hypertension and diabetes

Abstract: Diabetes and hypertension have become the primary causes of chronic kidney disease worldwide. However, there are no established markers for early diagnosis or predicting renal prognosis. Here, we investigated the expression profiles of DNA repair and DNA methylation factors in human urinederived cells as a possible diagnostic or renal prognosis-predicting marker. A total of 75 subjects, aged 63.3 ± 1.9 years old, were included in this study. DNA and RNA were extracted from 50 mL of urine samples. We evaluated … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 15 publications
(20 citation statements)
references
References 25 publications
(18 reference statements)
0
17
0
Order By: Relevance
“…The same holds true for factors involved in other forms of DNA maintenance such as the KEOPS complex (Braun et al, 2017; Hecker et al, 2009) or KAT5, a contributor to DNA methylation and non-homologous endjoining repair (Hishikawa et al, 2019). The Itoh group further linked the proteinuric phenotype to DNA double strand breaks and methylation in the promotor region of slit diaphragm protein nephrin and established an association of DNA double strand breaks in glomeruli of patients suffering from IgA nephropathy (Hayashi et al, 2020; Hishikawa et al, 2020). Our analysis adds considerably to this body of evidence, as we identify multiple factors of DNA maintenance, in particular of NER, to be transcriptionally altered in glomeruli of various renal diseases involving pronounced podocyte damage and loss.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The same holds true for factors involved in other forms of DNA maintenance such as the KEOPS complex (Braun et al, 2017; Hecker et al, 2009) or KAT5, a contributor to DNA methylation and non-homologous endjoining repair (Hishikawa et al, 2019). The Itoh group further linked the proteinuric phenotype to DNA double strand breaks and methylation in the promotor region of slit diaphragm protein nephrin and established an association of DNA double strand breaks in glomeruli of patients suffering from IgA nephropathy (Hayashi et al, 2020; Hishikawa et al, 2020). Our analysis adds considerably to this body of evidence, as we identify multiple factors of DNA maintenance, in particular of NER, to be transcriptionally altered in glomeruli of various renal diseases involving pronounced podocyte damage and loss.…”
Section: Discussionmentioning
confidence: 99%
“…Likewise, glomerular DNA damage was found to be associated with declining kidney function 12 and cells isolated from the urine of patients suffering from diabetes and hypertension showed increased levels of DNA strand breaks 13 . However, a link between DNA damage and podocyte loss, to date, remains unclear.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Studies performed on podocytes derived from mice models of diabetic kidney disease showed decreased expression of KAT5 , that is responsible for acetylation of ataxia telangiectasia mutant (ATM), a key protein in DNA-DSB repair. The decreased activation of ATM resulting from diminished expression of KAT5 disturbs the control of checkpoints connected with cell cycle arrest, DNA repair or apoptosis [ 140 , 141 ]. It was also demonstrated that insulin via the inactivation of glycogen synthase kinase-3 (GSK-3β) led to impaired DNA repair.…”
Section: Molecular Insight Into Anti-cancer Activity Of Vitamin Dmentioning
confidence: 99%
“…Instead, the researchers have been more interested in developing biomarkers for one specific comorbidity, kidney disease ( Table 9 ) [ 173 , 174 , 175 ]. Because urine examinations identify changes in gene expression in urine-derived cells [ 176 ], they may be helpful for the noninvasive assessment of kidney condition and prediction in early T2D [ 177 ].…”
Section: Epigenomics Biomarkers For T2dmentioning
confidence: 99%